2005
DOI: 10.1371/journal.pgen.0010051
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Value of Recombination Is Constrained by Genome Modularity

Abstract: Genetic recombination is a fundamental evolutionary mechanism promoting biological adaptation. Using engineered recombinants of the small single-stranded DNA plant virus, Maize streak virus (MSV), we experimentally demonstrate that fragments of genetic material only function optimally if they reside within genomes similar to those in which they evolved. The degree of similarity necessary for optimal functionality is correlated with the complexity of intragenomic interaction networks within which genome fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 31 publications
7
110
0
Order By: Relevance
“…It has been shown that selection against heterologous gen combinations increases as host colonization progresses along the infection cycle of Cucumber mosaic virus [32], affecting the frequency of genetic exchange. This explains that recombinants and reassortants are often found at low frequencies [33,34], although the frequency of particular combinations may be dependent on agro-ecological factors [17,19], and support the hypothesis of co-adaptation of gene complexes within the viral genomes [32,35].…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcsupporting
confidence: 65%
“…It has been shown that selection against heterologous gen combinations increases as host colonization progresses along the infection cycle of Cucumber mosaic virus [32], affecting the frequency of genetic exchange. This explains that recombinants and reassortants are often found at low frequencies [33,34], although the frequency of particular combinations may be dependent on agro-ecological factors [17,19], and support the hypothesis of co-adaptation of gene complexes within the viral genomes [32,35].…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcsupporting
confidence: 65%
“…Empirical studies with a small plant virus suggest that the successful inheritance of a particular genetic fragment is inversely proportional to and constrained by its number of intragenome interactions (23). CoV transcription networks involve complex interactions among the viral replicase complex, cis and transacting sequence motifs, and perhaps host factors.…”
Section: Discussionmentioning
confidence: 99%
“…In virus evolution, role of genetic recombination is dynamic (Martin et al, 2005). One of the prospective benefits of such recombination is in sexual reproduction in order to access the joint genetic resources of distantly unrelated and related viral species (Rice, 2002;Keightley and Otto, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, at this time no evidence is available to propose that intergeneric trans-encapsidation is responsible for vector inspecificity, although by replacing/flip-flop the CP genes betwixt two geminiviruses related to distant genera lead to a change in vector species for virus transmission (Briddon et al, 1990). Specifically, it is obvious that in foreign genetic background viral genome regions that have hardly minor genetic connections with other viral genome regions perform better functions than do those with wide-ranging interaction networks (Martin et al, 2005;Lefeuvre et al, 2007;Woo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%